OP0270 Iga anti-ccp antibodies are detectable in the saliva but not sputum of individuals at-risk of developing rheumatoid arthritis. (12th June 2018) - Mankia, K.; Pentony, P.; Hunt, L.; El-Sherbiny, Y.; Duquenne, L.; Corscadden, D.; Do, T.; Meade, J.; Devine, D.; Emery, P.
Abstract : Background: Recent evidence suggests the initiation of rheumatoid arthritis (RA) – related autoimmunity may occur by local citrullination at the oral mucosa and lungs. IgA antibodies are the hallmark of mucosal immunity; the majority of saliva IgA antibodies are locally produced whereas IgG antibodies are largely serum derived(. 1 Furthermore, IgA anti-CCP antibodies have recently been described in the sputum of at-risk individuals(. 2 The relative importance of the oral and lung mucosa in disease initiation is, however, unclear and the prevalence of saliva and sputum anti-CCP antibodies in the same at-risk individuals has not been reported. Objectives: To investigate the prevalence of IgA anti-CCP antibodies in the saliva and sputum of seropositive individuals at risk of developing RA. Methods: Anti-CCP positive individuals with no evidence of clinical synovitis (CCP+), anti-CCP positive RA patients (RA) and healthy controls (HC) matched for age and smoking status were recruited. Unstimulated saliva and serum samples were collected. Induced sputum samples were obtained using 7% saline via ultrasonic nebuliser (UltraNeb 3000 DA, Devilbiss, Germany). Sputum was mixed with phosphate buffered saline, mechanically disrupted and centrifuged to obtain supernatant. IgA and IgG anti-CCP antibodies (anti-CCP2, immunocap assay, Phadia) were measured in all saliva, sputum and serum samples. IgA and saliva/sputum IgG anti-CCP titres exceeding the 95th centile in HC were considered positive. Results: 55 CCP+, 40 RA and 32 HC were recruited and had saliva and serum collected. 24 CCP+, 14 RA and 22 HC had sputum and serum collected. Of these, 23 CCP +and 7 RA patients provided simultaneous saliva, sputum and serum samples. 8/55 (15%) CCP +and 10/40 (25%) RA patients had positive saliva IgA anti-CCP levels compared with 1/31 (3%) HC. 23/54 (43%) CCP +and 21/48 (44%) RA patients had positive serum IgA anti-CCP levels compared with 1/32 (3%) HC (table 1). Of note, 7/18 (39%) patients with a positive saliva IgA anti-CCP test had a negative serum IgA anti-CCP test, suggesting localised production and accumulation of IgA anti-CCP antibodies rather than transfer from the serum. Only 1/24 CCP+ (4%) and 1/14 (7%) RA patients had positive sputum IgA anti-CCP levels. No patients had IgA anti-CCP detectable in both saliva and sputum samples. Conclusions: We found an increased prevalence of saliva but not sputum IgA anti-CCP antibodies in seropositive at-risk individuals. These findings support the concept that localised RA-related autoimmunity in at risk individuals can be site specific. IgA anti-CCP antibodies at the oral mucosa precede arthritis and may represent an important step in the initiation and propagation of disease. References: [1] Brandtzaeg P. Ann NY Acad Sci 2007. [2] Willis, et al. Arthritis Rheum2013. Disclosure of Interest: None declared